MEKANISME PASAR DALAM PERSPEKTIF EKONOMI ISLAM - DJAWAHIR HEJAZZIEY (Al Qalam, 2011)
Islamic economy views that the states, markets, and individuals should be in the equilibrium state. One may not become more inferior than other ones so that one is more dominant than other ones. The freedom of markets is guaranteed in Islam. The market is free to determine the production ways and prices. Disturbances causing the defects of market balance should be avoided. However, because it is difficult to find the market which can fairly run alone, the distortion of market is frequently happened so that it can harm many parties. Therefore, Islam permits the state to interfere the market to make the market becoming normal. The market which is allowed to run alone without any control causes the domination of market merely by several parties, such as the capital owners, the infrastructure ruler, and the information owners asymmetric information also be come problems which could not be solved by market. The duty of the state is to regulate and to control economy, to ensure the competition of market run perfectly, to organize well-distributed information and the justice of economy.Its role as the organizer does not, at moment's notice, make it dominant because the state may not disturb the market which has run proportionately. Its role just applies when distortion in market happens. Key Words: market mechanism, Islamic Economy